HEXACO Traits, Emotions, and Social Media in Shaping Climate Action and Sustainable Consumption: The Mediating Role of Climate Change Worry - Stefanos Balaskas (Psychology International)
Climate change is an irreversible crisis that urgently calls for social transformation to protect human livelihood and environmental stability. Establishing awareness, building environmental literacy, and citizens’ mobilization are the steps toward sustainable change in giving a legacy of hope to future generations. This research explores major psychological and social drivers of pro-environmental behavior, considering the influence of HEXACO personality traits, climate anxiety (CCW), and social media engagement (SMI) on sustainable consumption (SC) and climate action intentions (CCI). Our findings revealed th eco-guilt (EGQ) and environmental empathy (EE) are immediate drivers for climate action, while long-term nurturance of eco-grief (ECOG) leads to engagement, supporting the notion that different emotions uniquely contribute to pro-environmental intentions. In terms of personality predictors, HEXACO’s traits of emotionality (E), honesty-humility (HH), and openness (O) are revealed to be significant, with emotionality also moderating the relationship between eco-grief and climate change action. The results reveal that connectedness to nature (CTN) and moderate levels of climate anxiety synergistically promote sustainable consumption intentions, while demographic factors such as gender, education levels, and exposure to social media moderate these intentions. Females also show a higher level of climate action intention in response to eco-guilt and eco-grief, while individuals with higher levels of education are more responsive to climate-related social media content, increasing their sustainable consumption behaviors. In exploring such interactions, this study aims to add to the understanding of what drives people toward valued environmental behaviors and, in turn, to inform effective climate advocacy, education, and personality-driven strategies to promote environmental engagement.